2010
DOI: 10.1007/s10661-010-1495-3
|View full text |Cite
|
Sign up to set email alerts
|

Choice of macroinvertebrate metrics to evaluate stream conditions in Atlantic Forest, Brazil

Abstract: The development of biomonitoring programs based on the macroinvertebrate community requires the understanding of species distribution patterns, as well as of the responses of the community to anthropogenic stressors. In this study, 49 metrics were tested as potential means of assessing the condition of 29 first- and second-order streams located in areas of differing types of land use in São Paulo State, Brazil. Of the sampled streams, 15 were in well-preserved regions in the Atlantic Forest, 5 were among sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 45 publications
3
51
0
4
Order By: Relevance
“…This supports the results of recent studies that have shown a relationship between these biodiversity indices and environmental gradients in the Neotropical region (e.g., Suriano et al, 2011). It has been generally argued that a significant relationship between community-based response variables and spatial variables indicates that factors other than the environmental predictors are important, such as colonization processes, unmeasured local environmental variables that are spatially autocorrelated, and dispersal pathways among habitat patches (Peres-Neto and Legendre, 2010).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This supports the results of recent studies that have shown a relationship between these biodiversity indices and environmental gradients in the Neotropical region (e.g., Suriano et al, 2011). It has been generally argued that a significant relationship between community-based response variables and spatial variables indicates that factors other than the environmental predictors are important, such as colonization processes, unmeasured local environmental variables that are spatially autocorrelated, and dispersal pathways among habitat patches (Peres-Neto and Legendre, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Most of the remnant fragments are located on the steep slopes of mountains , and composed of small (<50 ha) and structurally isolated (mean distance 1 440 m) habitat patches that suffers from edge effects (Ribeiro et al, 2009). Twenty streams were located within protected areas and nineteen were located in regions occupied by extensive sugarcane monoculture, pastures, Eucalyptus plantations (L'Hér, Myrtaceae) and banana plantations (see: Suriano et al, 2011;Corbi et al, 2013).…”
Section: Study Areamentioning
confidence: 99%
“…Following the protocol established by Suriano et al (2010), we selected 100 meter-long stretches of stream and took six samples using a Surber sampler with an area of 30 × 30 centimeters (total of 54 m² per stream) and a mesh opening of 250 µm. Additionally, for 30 seconds we scanned with a D net to sample microhabitats where a Surber sampler is hard to use.…”
Section: Sampling and Identification Of Chironomidae Larvaementioning
confidence: 99%
“…This is also seen in our results (Table 5). The use of diversity and richness indices as appropriate metrics to evaluate stream conditions is defended by Suriano et al (2010) who analyzed 49 metrics to assess the conditions of streams of São Paulo State. Similarity measures are among the most common (and accepted) metrics for comparing sites or samples (Diserud and Ødegaard 2007).…”
Section: Chironomidae Faunamentioning
confidence: 99%